2018
DOI: 10.1186/s13052-018-0476-y
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between body mass index and children’s presentations to a tertiary pediatric emergency department

Abstract: BackgroundThe child obesity and its complications are associated with an alarming increased health care use, including the emergency department (ED). We evaluated the effects of the obesity and overweight in children admitted to ED, especially in patients with injury diagnosis.MethodsA retrospective study of patients aged 6–18 years was conducted. Patients were categorized into normal weight (body mass index, BMI < 85th); overweight (BMI ≥ 85th e < 95th); obesity (BMI ≥ 95th). Multiple logistic analysis was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
(29 reference statements)
0
4
0
2
Order By: Relevance
“…The evidence regarding a link between obesity and risk of accidents remains inconclusive. Whereas Lynch et al 23 reported that obesity seemed to increase such risk, Ferro and colleagues30 concluded that obesity played a protective role. Such role, however, probably reflects the inverse relationship between obesity and physical activity levels among children.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence regarding a link between obesity and risk of accidents remains inconclusive. Whereas Lynch et al 23 reported that obesity seemed to increase such risk, Ferro and colleagues30 concluded that obesity played a protective role. Such role, however, probably reflects the inverse relationship between obesity and physical activity levels among children.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic kidney disease, low bone mineral density, glucocorticoid use, vitamin D deficiency, and dietary factors have been implicated in the pathophysiology of fracture . Vitamin D deficiency has been associated with childhood obesity, obesity being implicated in pediatric fracture pathophysiology in retrospective clinical and basic science studies …”
Section: Introductionmentioning
confidence: 99%
“…(17)(18)(19)(20)(21)(22) Vitamin D deficiency has been associated with childhood obesity, obesity being implicated in pediatric fracture pathophysiology in retrospective clinical and basic science studies. (23)(24)(25)(26)(27)(28)(29)(30)(31) Less evidence exists for the impact of preschool obesity upon future health, with previous studies including a wide age range of children producing conflicting results. (32) A focused study of the association between preschool obesity and fracture risk offers the opportunity to better understand the impact of obesity in early life.…”
Section: Introductionmentioning
confidence: 99%
“…An Italian study found that obese children have an increased fracture risk at ages 6-12 years. The authors suspect reduced bone density as a result of reduced physical activity, biomechanical factors, and vitamin D deficiency to be the reason for the increased fracture risk (Ferro et al 2018). However, a Danish study found that the prevalence rates of obesity among children have plateaued and even shown a tendency for decline 1983, 1997, Hedström et al 2010, Rennie et al 2007, Meling et al 2009, Lempesis et al 2017.…”
Section: Discussionmentioning
confidence: 99%